An Efficient Hybrid MANET-DTN Routing Scheme for OLSR - Azzuhri, Saaidal Razalli; Ahmad, Harith; Portmann, Marius; Ahmedy, Ismail; Pathak, Ranjana (Kluwer (now part of Springer), 2016)
This paper presents a new hybrid protocol which combines the end-to-end routing of traditional wireless mobile ad-hoc networks (MANETs) with the store-carry-forward routing paradigm of delay-tolerant networks (DTNs). An extensive evaluation over a wide range of topologies, from highly connected to highly disconnected typologies, shows that this protocol can significantly improve performance in most cases. This newly developed protocol is named OLSR-Opportunistic (OLSR-OPP), and is an extension of the optimised link state routing (OLSR) protocol. Our newly proposed protocol combines the efficiency of the OLSR-based MANET end-to-end routing and the flexibility of the store-and-forward concept of DTNs. Our protocol functionality was validated with a simple scenario setup and worked according to our specification. We then extensively evaluated our proposed protocol over a systematically selected range of topologies and mobility scenarios, ranging from very high to very minimal network connectivity, and effectively demonstrated its significant improvement in terms of packet delivery ratio over traditional MANET and DTN routing. The simulation result shows that the OLSR-OPP significantly outperforms the original OLSR and DTN spray-and-wait protocol. The results further demonstrate the trade-off between protocol performance and overheads via the tuning of the copy_count OLSR-OPP protocol parameter.